THE EFFECT OF OUTPATIENT PHARMACEUTICAL SERVICE QUALITY ON PATIENT LOYALTY THROUGH PATIENT SATISFACTION OF KARSA HUSADA GENERAL HOSPITAL BATU - Insani, Septa Dwi; Hakim, Lukman; Widyaningrum, Kurnia (Universitas Brawijaya, Indonesia, 2017)
Pharmacy Department an important role in the hospital service because almost 80% of patients will have medical prescription. However, the pharmacy department in this hospital has a different between the standard which have been set by the Government and the implementation of pharmacy service. Furthermore, after the intervention applied, it showed the decreased number of waiting time for medicine and also this decline has influence the patient satisfaction. In Karsa Husada general hospital the percentage of patient satisfaction is about 68.50% and the patients who satisfy with the service said that they will visit the hospital again. The purpose of this research is to find out whether the quality improvement of outpatients pharmacy service influence the patient loyalty through patient satisfaction. The method of this research was quantitative research with observational analytical study and used the cross sectional as the approach. The population of this research is about 1.143 patients who have been received outpatient pharmacy service, meanwhile the sample is about 89 patients who are not using insurance. The data analyzed using PLS which using SMART PLS program. Based on the result, it showed that the quality improvement of pharmacy service has positive effect and also significant towards patient satisfaction. However, the result showed that the quality improvement of pharmacy service and patient satisfaction has positive effect but not significant towards patient loyalty, then it also showed that the quality improvement of pharmacy service has positive effects but not significant towards patient loyalty through patient satisfaction in Pharmacy Department on Karsa Husada general hospital. Suggestions that can be given to the hospital that is to keep facilities and do strategy to prevent medicine void.